The influence of regional Italian images on consumer behaviour: a study of consumers in Germany - Simon Fauser; David Agola (Italian Journal of Marketing, 2021)
The purpose of this paper is to investigate the influence of regional images of Italy on the purchase probability of wine. Instead of regarding country image as a homogeneous national construct, this article focuses on revealing regional differences in Italian country image and investigating whether they are related with purchase probability. Moreover, several scholars state, that the development of larger regional brands can improve consumer choice especially for the product wine. In the light of growing global competition from 'New World' wine countries and simultaneously decreasing competitivity of the main European wine-producing countries (including Italy), the possibility to actively shape the development of regional brands and thereby potentially strengthening the competitive advantage within the European Union and on a global level, seems to offer an adequate approach to maintain the leading role of Italian wine producers in European and international trade. Therefore, this study aims to test, whether using larger regions (and not specific wine regions) as origin information for wine is applicable and improving consumer choice. The empirical framework was tested on a random sample of consumers living in Germany and comprises (a) the description of image differences between Northern and Southern Italy, (b) measuring the influence of regional indication of origin on purchase probability, (c) determining the predictive value of image components for purchase probability, and (d) the investigation of moderation effects of country knowledge on the results. Data from 388 respondents were analysed using multiple linear regression and paired t test. Results show significant image differences, which affects purchase probability. It is shown that the image of Southern Italy does not provide respondents with a suitable decision-making heuristic for buying wine. Furthermore, country knowledge negatively influences the predictive value of the measured regional image for purchase probability. As the predictive value of Southern Italian image does not contribute to the explanation of purchase probability, the present work corroborates the hypothesis of region-specific tendencies in the relationship between regional Italian image and consumer behaviour. Thus, this work provides a fundamental understanding of the regional composition of the Italian country image. It therefore serves practitioners as a decisional basis for the utilization of origin-related product information.
Keywords: 330; Country of origin; International marketing; Mezzogiorno; Consumer behaviour